Academic Fraud Behavior From The Diamond Fraud Perspective - Leriza Desitama Anggraini; Imelda Saluza; Andini Utari Putri; Sinta Habibah (Jurnal Akuntansi, 2024)
This research aims to determine the influence of pressure, opportunity, rationalization, capability on academic fraud. Academic fraud that occurs in the university environment includes cheating, copying from the internet, taking exams together and even using assistant for final assignments and theses. This research is quantitative research using primary data that researchers obtained from distributing questionnaires. The samples taken were obtained randomly from each batch of private university accounting students in Palembang City. The researcher processed the questionnaire using SPSS software. The research results stated that all the variables used had a simultaneous effect. The variables pressure, opportunity, capability partially have a significant effect on fraudulent behavior. In the rationalization variable, it can be seen that the significance of the results is greater than the predetermined significance, so that the rationalization variable has no effect on fraudulent behavior at private universities in Palembang City.